Apply Optimarin Ballast System for Vietnam’s Fleet to Prevent Sea Pollution from Non-Indigenous Aquatic Species - Dinh-Chien Dang; Ming-Hung Shu; Bi-Min Hsu; Thanh-Lam Nguyen; Phung-Kim Truong; Viet-Thanh Nguyen (Institute of Advanced Engineering and Science, 2016)
Marine species are usually transported from one area to another by the ballast water used to provide safe operation for vessels. After entering a new environment, they may cause damage to the local ecosystem, leading to the disruptions of the entire marine ecosystem, and seriously affecting not only biodiversity but also several industries such as fishing and aquaculture. Therefore, the United Nations (UN) considers the presence of non-indigenous oceanic species to be one of the top four serious threats to the global environment; and, how to effectively control the non-indigenous aquatic species has captivated the special attentions of several scientists worldwide. With the significant development in the maritime industry, strict requirements the control and management of ships’ ballast water and sediments set by The UN's International Maritime Organization (IMO) have well shaped the trend in installing ballast water treatment systems. Among them, Optimarin Ballast System is preferably used in practice. However, currently, Vietnam’s fleets use a different chemical method which is not utilized elsewhere in the world. Because it is not environmentally friendly and its effectiveness hasn’t been validated yet, this paper suggests the application of OBS in the Vietnam’s fleet in order to prevent sea pollution from non-indigenous aquatic species and minimize its associated negative impacts as well as make the Vietnam’s fleet comply with IMO requirements in protecting the global environment for sustainable development.